Dietary diversity and wasting among children aged 06-23 months and its' associated factors in Dalit and Non Dalit: A cross sectional comparative study of Dhanusha district, Nepal. - Kumar Sah, Anil. (Tufts University. Tisch Library., 2020)
The objective of this research is to assess status and identify factors associated with dietary diversity and wasting among children aged 6-23 months in Dalit and Non Dalit of Dhanusha District.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy